2014
DOI: 10.1016/j.gheart.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Acute Coronary Syndrome in a Multiethnic Asian Population: Results of the Malaysian National Cardiovascular Disease Database—Acute Coronary Syndrome (NCVD-ACS) Registry

Abstract: Our study showed significant sex differences in the demographic characteristics, risk factors, treatments, and outcomes of ACS. More importantly, in ACS patients, we found evidence of suboptimal treatments and interventions in women versus men. Our findings provide an opportunity to narrow the sex gap in the care of women with ACS in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
1
20
0
4
Order By: Relevance
“…This situation is unavoidable, as the incidence of MI among the Malaysian population is more prevalent in men than in women. 51 , 52 Another plausible explanation of medication nonadherence among men is the apprehension of the medication side effects (erectile dysfunction with β-blockers), 18 as evidenced in rigorous clinical trials. 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…This situation is unavoidable, as the incidence of MI among the Malaysian population is more prevalent in men than in women. 51 , 52 Another plausible explanation of medication nonadherence among men is the apprehension of the medication side effects (erectile dysfunction with β-blockers), 18 as evidenced in rigorous clinical trials. 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…Prescribing variations across groups of interest in NSTEMI patients were examined using binary logistic regression adjusting for covariates and presented as odds ratio (OR) and 95% confidence intervals (CI). Covariates chosen were those shown to impact prescribing trend such as age group, gender [19], ethnicity [9], calendar year, geographical regions [22], presence of risk factors and presence of co-morbidities [1, 2]. For geographical region, the Western Peninsular was chosen as the reference as this region has the most tertiary centers for CV referrals in this country [24].…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the prescribing of evidence-based pharmacotherapies has been described for STEMI [18] while less is known on NSTEMI. In acute interventions of AMI, women [19] and elderly patients [20] were less likely to receive optimal management compared to men and younger patients while no significant variations across ethnicities were observed [21]. Regional variations have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Many ACS studies have shown women to be older and with higher incidences of comorbidities at presentation [ 8 ], [ 9 ]. In Asian populations, sex differences in the demographic characteristics, risk factors, treatments, and outcomes of ACS was demonstrated in a study in Malaysia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%